The challenges for social work under the pressures of neoliberal policies: a study of policy changes in the Italian probation - Ruggero Capra (Social Work and Society)
The actions or reactions of social workers toward the challenges of neoliberal ideology in Italian probation policies will be explored through the analysis of an episode related to the approval of a draft Probation Act: the so-called Mastella Act. The results of a qualitative analysis of social workers' statements and opinions concerning the debate surrounding this episode confirm Trivellato and Lorenz's (2010) findings of the tendency of Italian social workers to underestimate political aspects in their work. The controversy over the Mastella draft Act represents a rich field of research because it traces the effects of a general shift from welfare to control in Italian social politics. In confirming the hypothesis, the findings point towards a one-sided understanding of social workers' professional role which underestimates the importance of political analysis against individualized casework, thereby rendering the profession vulnerable to substitution by the police force.